Pengembangan Game edukasi berbasis Augmented Reality sebagai Media Pembelajaran Aksara Jepang - Marwa Sulehu (Jurnal Minfo Polgan, 2023)
Common problems faced by students in learning Japanese script in Indonesia include difficulty constructing sentences, distinguishing between hiragana and katakana letters, speaking Japanese, and using vocabulary. To overcome this obstacle, research proposes the development of learning media based on Augmented Reality (AR) with the concept of educational games. Involving the SMUNEL Japanese Community at SMA Negeri 5 Makassar, the research used qualitative methods with discussion, observation and documentation. The research results identified internal factors, namely the decline in enthusiasm for learning, and external factors, namely the need for innovative media, as the main problem. The proposed solution is an educational game-based AR application to introduce Japanese characters. Application testing showed a positive response, with 90% of respondents agreeing that this application increases interest in learning and helps distinguish basic Japanese letters. It is hoped that this research will make a significant contribution in providing innovative and interactive Japanese language learning alternatives through the use of AR technology.